Pengaruh Green Marketing Dan Citra Merek Terhadap Keputusan Pembelian Produk Le Minerale - Anggraini, Selvia Sapta; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2023)
This study aims to determine the effect of green marketing and brand perception on consumer decisions to buy le minerale beverage products in city X. This type of research is explanatory research, taking samples through nonprobability sampling technique. These data were carried out and retrieved through the distribution of questionnaires to consumers who love le mineral products. This research uses quantitative methods. With a t value of 10.077 > 1.98525 (t table) and a sig value of 0.000, the findings of this study indicate that green marketing variables influence consumer decisions to buy Le Minerale products. With a t value of 9.010 > 1.98525 (t table), the findings of the brand image variable indicate that brand image has a significant effect on consumer decisions to buy Le Minerale products. In addition, green marketing and brand perception, with a calculated f value of 70.954> 3.09 (F table), have a considerable impact on purchasing decisions. However, the green marketing variable, which is equivalent to 51.9% of the total, has a stronger influence than the brand image variable. From the data above, we can conclude that the better the green marketing, the more consumers' interest in buying will increase.